The Effect of Co-Branding on Purchasing Decisions in the Indonesia Ice Cream Industry - Wildan Army Abdillah; Dzarin Gifarian Khaulani (Islamicate Institute, 2020)
This study aims to determine the effect of Co-Branding on purchasing decisions in Walls Ice cream products. The total sample in this study was 57 people. This research was conducted in less than one year, therefore the research method used was a cross-sectional study. Based on the variables studied, the type of research used is descriptive and verification research. The research method used is the explanatory survey method. This research is sourced from primary data obtained using several question items using google form. This article found that Co-Branding has a positive and significant influence on purchasing decisions. This shows that Co-Branding can influence purchasing decisions and will improve sales performance.